Unraveling the relationship between coaching behavior and athlete burnout in Malaysian university-level athletes / Hafiz Izzuddin Zulkifle and Azman Ahmad Tajri - Zulkifle, Hafiz Izzuddin; Ahmad Tajri, Azman (Universiti Teknologi MARA, Negeri Sembilan, 2025)
This study investigates the correlation between coaching behavior and athletes' burnout levels among Karisma athletes at UiTM Negeri Sembilan 2024. It aims to identify specific coaching behaviors, assess athletes' burnout levels, and analyze their relationship, addressing gaps in understanding the dynamics affecting athlete performance and well-being. This non-experimental, quantitative study used descriptive and correlation analyses to examine coaching behavior and athlete burnout among 136 Karisma athletes from UiTM Negeri Sembilan, selected via the Krejcie and Morgan table. Data were collected using the Coaching Behavior Scale for Sport (CBS-S) [1] and Athlete Burnout Questionnaire (ABQ) [2].